THE ROOTS OF JAPANESE LEGAL TERMINOLOGY - HORIE, Yuki (Comparative Legilinguistics, 2010)
During the Meiji era, Japan began its modernization and the Western culture was introduced to Japan. Japan had to construct a modern society, fusing complicatedly with a model of the Japanese tradition. In the legislation field, beginning with the Constitution of the Empire of Japan, the establishment of the first unified nationwide law was attempted in this period. In particular concerning the civil code, The French Code (later German Code) was considered as the most comprehensive code, and its translation was made and edited as a Japanese Civil Code. However, translating the original concepts which had not existed in Japan was a very difficult task. They coined words preserving the original sequence of elements and as a result there is a gap between the European legal terms and the Japanese ones especially in translation. The current legal terminology was made based on such a historical background, in consequence it has become less familiar to Japanese people. I would like to consider theses problems on some examples.